2018
DOI: 10.3390/molecules23040935
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity and Biological Activities of Diterpenoids Derived from Euphorbia fischeriana Steud

Abstract: Diterpenoids are the focus of natural product drug discovery because of their great structural diversity and pronounced biological activities. Euphorbia fischeriana Steud is a Chinese traditional medicinal herb for curing edema, ascites, and cancer. This plant contains rich diterpenoids. Based on the carbon skeleton and substituents, it can be classified into thirteen subtypes: ent-abietane, daphnane, tigliane, ingenane, ent-atisane, ent-rosane, ent-kaurene, ent-kaurane, secotigliane, lathyrane, ent-pimarene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…Previous studies (Huang et al, 2014; Hua et al, 2017) have reported anti-feeding activity of selected Euphorbia diterpenoids against generalist plant-feeding insects, Spodoptera exigua (Hübner, 1808) and Helicoverpa armigera (Hübner, 1808). In vitro , Euphorbia diterpenoids are known to induce different immunomodulatory responses through the selective modulation of PKC including the release of prostaglandins and pro-inflammatory cytokines such as TNF-α, interleukin-6, and interleukin-1β (Smith and Meldrum, 1992; Berman, 2012; Uto et al, 2012; Jian et al, 2018; Zhang et al, 2019). Here, we evaluated the pro-inflammatory potential of the crude Euphorbia extracts by measuring the capacity of small extract fractions, corresponding to compounds or compound groups in each of the 43 Euphorbia species that modulate in vitro TNF-α release from PBMCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies (Huang et al, 2014; Hua et al, 2017) have reported anti-feeding activity of selected Euphorbia diterpenoids against generalist plant-feeding insects, Spodoptera exigua (Hübner, 1808) and Helicoverpa armigera (Hübner, 1808). In vitro , Euphorbia diterpenoids are known to induce different immunomodulatory responses through the selective modulation of PKC including the release of prostaglandins and pro-inflammatory cytokines such as TNF-α, interleukin-6, and interleukin-1β (Smith and Meldrum, 1992; Berman, 2012; Uto et al, 2012; Jian et al, 2018; Zhang et al, 2019). Here, we evaluated the pro-inflammatory potential of the crude Euphorbia extracts by measuring the capacity of small extract fractions, corresponding to compounds or compound groups in each of the 43 Euphorbia species that modulate in vitro TNF-α release from PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Euphorbia diterpenoids are known to induce different immunomodulatory responses in vitro through the selective modulation of PKC including the release of prostaglandins and pro-inflammatory cytokines such as TNF-α, interleukin-6, and interleukin-1β (Smith and Meldrum, 1992; Berman, 2012; Uto et al, 2012; Jian et al, 2018; Zhang et al, 2019). Both vertebrates and invertebrates produce cytokines, and it is likely that they exhibit similar functions both in insect as well as mammalian cells (Adamo, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Euphorbia helioscopia L. is used in the traditional Chinese medicine in situations of bacillary dysentery, osteomyelitis, and malaria [53]. In Uyghur medicine, China, E. resinifera O.Berg is recurrently employed to suppress tuberculosis, toothache, and chronic pain [54], while E. fischeriana have been used as a remedy for cancer, ascites, and oedema [55], and E. granulata Forssk. is utilized against intestine worms, oedema, cough, blood impurities, and renal diseases [56,57].…”
Section: Traditional Medicine Uses Of Euphorbia Plantsmentioning
confidence: 99%
“…Euphorbia fischeriana is a perennial herbaceous plant of euphorbiaceae found mainly in the Northeast of China. The plant’s dried roots, named “Lang-du” in traditional Chinese medicine, have many pharmacological effects of eliminating phlegm, antitubercle, and anti-cancer [1,2,3,4,5]. The Ebracteolata Compound B, ECB (2,4-dihydroxy-6-methoxy-3-methyl acetophenone), from the acetophenone family, is of concern and in great demand in the field of medicine due to its obvious anti-tuberculosis activity [6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%